The vicious circle of treatment-induced toxicities in locally advanced head and neck cancer and the impact on treatment intensity. (August 2017) - Bossi, Paolo; Cossu Rocca, Maria; Corvò, Renzo; Depenni, Roberta; Guardamagna, Vittorio; Marinangeli, Franco; Miccichè, Francesco; Trippa, Fabio
Abstract: The intensity of the available treatment approaches for locally-advanced head and neck cancer (HNC) is at the upper limit of tolerance of acute toxicities. Several factors including breakthrough cancer pain, mucositis, dysphagia, local and systemic infections, and nutritional problems are related to treatment intensity. Particularly, pain, as symptom directly associated with the disease or combined with other treatment-related factors, has a major impact on quality of life of HNC patients and ultimately can influence the efficacy of treatments in HNC. Here, a Multidisciplinary Board of Italian Experts has addressed these issues, with the aim to identify the unmet need and appropriate strategies for the maintenance of optimal treatment intensity in HNC.